Potential Socio-economic Impacts of a Development Intervention in the Rural Setting - Timseena, Bhanu (Economic Journal of Nepal, 2005)
The development intervention in transport and communication sector in any underdeveloped/rural areas brings a lot of change in the social as well as economic life of the people. The impact of development infrastructures may be direct or indirect (Cracknell,2000). There will be three types of spatial impacts: first, negative impact during initial stage and positive in the final; second, completely negative; and third, completely positive could be assumed in any development projects. People are connected globally via trans-national traveling. It is not necessary that all projects have completely negative or completely positive impacts. Most of them stay between partially negative and partially positive. This paper is an assessment of recently proposed New International Airport (NIA) in Nepal. The aim of searching for new international airport out of Kathmandu valley was to decentralize the development opportunities and export promotion of Nepalese industrial product from Terai. The increasing flow of international tourists as trekkers and pilgrims outside Kathmandu inspired Civil Aviation Authority to explore the possibility of an international airport to connect the world with rural Nepal.Economic Journal of Nepal Vol.28(4) 2005 pp.215-230